Intentions of public school teachers in British Columbia, Canada to receive a COVID-19 vaccine. (August 2021) - Racey, C. Sarai; Donken, Robine; Porter, Imogen; Albert, Arianne; Bettinger, Julie A.; Mark, Jennifer; Bonifacio, Lizl; Dawar, Meena; Gagel, Mike; Kling, Rakel; Mema, Silvina; Mitchell, Hana; et al.
Abstract: Background: To control the COVID-19 pandemic high vaccine acceptability and uptake will be needed. Teachers represent a priority population to minimize social disruption and ensure continuity in education, which is vital for the well-being and healthy development of youth during the pandemic. The objective of this analysis was to measure public school teachers' intentions to receive a COVID-19 vaccine in British Columbia (BC), Canada. Methods: A population-wide cross-sectional online survey from August to November 2020 asked all BC public school teachers with an available email address how likely they were to receive a COVID-19 vaccine. Two multivariable logistic regression models explored separately sociodemographic and vaccine hesitancy predictors for intention to receive a COVID-19 vaccine. Results: A total of 5, 076 teachers participated. The majority, 89.7%, reported they were likely or very likely to accept a COVID-19 vaccine. In multivariable regression, sociodemographic predictors of intention to be vaccinated included being male, having an educational background in science or engineering, and using reliable information sources on vaccination such as public health and health care providers. Teachers who reported lower levels of vaccine hesitancy, higher general vaccine knowledge, and belief that COVID-19 was a serious illness were more likely to intend to receive a COVID-19 vaccine. Conclusion: A high proportion of public-school teachers in BC intend to receive a COVID-19 vaccine. Continued monitoring of vaccine intentions will be important to inform public health vaccine implementation.